2020
DOI: 10.5194/bg-17-2441-2020
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton growth and consumption by microzooplankton stimulated by turbulent nitrate flux suggest rapid trophic transfer in the oligotrophic Kuroshio

Abstract: Abstract. The Kuroshio Current has been thought to be biologically unproductive because of its oligotrophic conditions and low plankton standing stocks. Even though vulnerable life stages of major foraging fishes risk being entrapped by frontal eddies and meanders and encountering low food availability, they have life cycle strategies that include growing and recruiting around the Kuroshio Current. Here we report that phytoplankton growth and consumption by microzooplankton are stimulated by turbulent nitrate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
5
21
0
1
Order By: Relevance
“…In the Tokara Strait, turbulent mixing and turbulent nutrient flux are enhanced in the surface/subsurface Kuroshio water due to flow-topography interaction, similar our observations in the Luzon Strait. Although our estimate of the chlorophyll a depletion rate includes many assumptions, its similarity to the estimate by Kobari et al 5 may suggest a common role of the strong turbulent mixing in the Kuroshio water on higher trophic level productivity. However, similar but relatively small estimates of phytoplankton growth rate in this study (0.16-0.33 d −1 ) implies that factors not considered here, such as the horizontal advection process, may necessary to be considered.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the Tokara Strait, turbulent mixing and turbulent nutrient flux are enhanced in the surface/subsurface Kuroshio water due to flow-topography interaction, similar our observations in the Luzon Strait. Although our estimate of the chlorophyll a depletion rate includes many assumptions, its similarity to the estimate by Kobari et al 5 may suggest a common role of the strong turbulent mixing in the Kuroshio water on higher trophic level productivity. However, similar but relatively small estimates of phytoplankton growth rate in this study (0.16-0.33 d −1 ) implies that factors not considered here, such as the horizontal advection process, may necessary to be considered.…”
Section: Discussionsupporting
confidence: 69%
“…Kobari et al 5 estimated high mortality rates of total phytoplankton due to grazing by zooplankton of 0.38-1.05 d −1 in the surface Kuroshio water from dilution experiments in the late-autumn Tokara Strait. The high mortality rates indicate rapid trophic transfer to zooplankton and suggest important roles of the topographically enhanced turbulent nutrient fluxes in the high biological productivity in the apparently oligotrophic Kuroshio 5 . They also estimated phytoplankton net growth rates of ≤ 0.55 d −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have recommended several physical mechanisms that might transport deep-water nutrients to the surface waters and trigger high plankton biomasses and activities in the KC. In the downstream area, the intrusion of nutrient-rich KC subsurface water onto the continental shelf (Liu et al, 2013;Hasegawa et al, 2019), the mesoscale lateral mixing of KC water with Oyashio water (Clayton et al, 2014), and the topographically induced turbulence mixing (Kobari et al, 2020) have been proposed as the mechanisms that might intensify biological biomass and production in the surface water. At the KC upstream area (Tsutsumi et al, 2020), findings have demonstrated that the high minerals fluxes and high surface Chl-a concentrations observed in the Luzon Strait could be ascribed to the strong turbulence mixing induced by the interaction of topography (i.e., steep oceanic ridges) and tidal current.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al (2019) used this method to demonstrate that the vertical mixing associated with rough topography at the Izu ridge elevated the nitrate flux and contributed to the nitrate component of the Kuroshio nutrient stream (Guo et al, 2013). Furthermore, Kobari et al (2020) conducted nutrient addition experiments in oligotrophic Kuroshio water to determine the effects of turbulent nitrate flux elevation in the Tokara Strait. They found a significant increase in microzooplankton grazing on phytoplankton, suggesting that such rapid and systematic trophodynamics support biological productivity in the Kuroshio.…”
mentioning
confidence: 99%